Low-valent dialkoxytitanium(ii): a useful tool for the synthesis of functionalized seven-membered ring compounds. Issue 29 (12th March 2021) - Bodinier, Florent; Sanogo, Youssouf; Ardisson, Janick; Lannou, Marie-Isabelle; Sorin, Geoffroy
Abstract : Herein, we describe unprecedented access to all-carbon or heterocyclic seven-membered ring frameworks from 1, 8-ene-ynes promoted by inexpensive low-valent titanium(ii ) species, readily available from a combination of Ti(OiPr)4 and Grignard reagent. Abstract : Herein, we describe unprecedented access to all-carbon or heterocyclic seven-membered ring frameworks from 1, 8-ene-ynes promoted by inexpensive low-valent titanium(ii ) species, readily available from Ti(OiPr)4 and Grignard reagent. A broad range of cycloheptane, azepane or oxepane derivatives has been obtained (19 examples) with moderate to good yields and an excellent selectivity (up to 95/5 d.r.).